2007
DOI: 10.1007/s00404-007-0473-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of ectopic pregnancy in the presence of a significant haemoperitoneum

Abstract: Our study demonstrates that with highly skilled anaesthetic and surgical teams, operative laparoscopy with its recognized advantages over laparotomy and is feasible in women with ruptured ectopic pregnancy and significant haemoperitoneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Although haemodynamically unstable patients were excluded from this study, there is enough evidence to suggest that laparoscopic surgery can be safely performed in these women. [11,12,19] Secondary and tertiary public hospitals should invest in skills training, laparoscopic equipment and instruments to enable laparoscopic surgery for women presenting with ectopic pregnancy. Operative laparoscopy on a 24-hour basis for the treatment of women with REP is feasible in a public hospital in resource-poor settings and should become standard treatment for the majority of women with this condition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although haemodynamically unstable patients were excluded from this study, there is enough evidence to suggest that laparoscopic surgery can be safely performed in these women. [11,12,19] Secondary and tertiary public hospitals should invest in skills training, laparoscopic equipment and instruments to enable laparoscopic surgery for women presenting with ectopic pregnancy. Operative laparoscopy on a 24-hour basis for the treatment of women with REP is feasible in a public hospital in resource-poor settings and should become standard treatment for the majority of women with this condition.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] However, the laparoscopic approach was superior to laparotomy in terms of significantly shorter operating time, [6,7] reduced intraoperative blood loss, analgesic requirement, time to normal activity, total hospital costs, [8] shorter hospital stay and quicker recovery in haemodynamically stable women. [9] Although some data suggest that laparoscopic surgery is feasible in women with significant haemoperitoneum, [10][11][12][13] to our knowledge there are no prospective randomised trials comparing laparotomy with laparoscopy in the surgical management of women with REP in any setting. The available evidence of the preferred mode of surgical treatment for women diagnosed with suspected REP is scanty and consists of retrospective trials, mostly with small numbers.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study spanning twelve years and 19 cases in one institution, primary laparoscopy was attempted in 84% of women with ovarian pregnancy . Another study reported that in 2006, all women with an ectopic pregnancy and significant haemoperitoneum were successfully treated laparoscopically …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, minimally invasive management has been widely accepted as having various benefits and become the trend for management [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%